Nina's Love Betrayal in The Drama Script The Seagull by Anton Chekov - Della Eka Putri; Sri Kusumo Habsari; Susanto Susanto (International Journal of Science and Applied Science: Conference Series, 2022)
Drama is a form of literary work that describes the reality of human life which is presented in the form of movement. In this case, one of the famous dramas "The Seagull" by Anton Chekhov who is a writer of short stories, non-fiction, and also a drama script is different from the majority of drama works in Russia in the 1800s which presented spectacle of comedy genre drama. Chekhov with his work The Seagull presents a drama genre tragedy or romantic tragedy. This study uses a qualitative research method with a descriptive qualitative analysis approach. Data collection will be carried out by means of in-depth interviews with predetermined sources, so this research will be seen the reason why Nina is betraying Constantine, even though Constantine loves Nina so much. Besides that is to find out more about the form or method used by Nina to get her wish.